Protecting the future of work : new institutional arrangements for safeguarding labour standards - Colfer, Barry; Harney, Brian, 1980-; McLaughlin, Colm; Wright, Chris F. (Emerald Publishing Limited, 2023)
Institutions such as trade unions that were once relied upon to protect workers' wages, conditions and job security are eroding. In response, new forms of worker protections are emerging. Protecting the Future of Work examines new forms of regulation that have emerged in response to increasing social concern about poor labour practices, growing inequality, and detrimental working conditions. It looks at how trade unions, community organisations and other actors have mobilised to raise public awareness and pressure businesses and governments to improve working conditions. Featuring a balance of texts on the changing nature of and the history of trade union change and transformation, the series Trade Unionism gives space for in-depth, detailed analysis and captures key themes on the nature of internationalism and trade unionism.
Keywords: Labor unions.; Labor laws and legislation.; Business & Economics -- Labor / Unions.; Trade unions.; elektronické knihy; electronic books